Healthcare professionals' proposed eHealth needs in elective primary fast‐track hip and knee arthroplasty journey: A qualitative interview study. Issue 23 (18th September 2019) - Jansson, Miia Marika; Harjumaa, Marja; Puhto, Ari‐Pekka; Pikkarainen, Minna
Abstract: Aims and objectives: To examine the lived experience of healthcare professionals providing care for patients with total hip and knee arthroplasty and to understand healthcare professionals' proposed eHealth needs in elective primary fast‐track hip and knee arthroplasty journey. Background: There is little evidence in nursing literature to indicate how to develop new eHealth services to support surgical care journeys. Evidence is particularly lacking regarding the development of eHealth solutions. Design: This was a qualitative interview study. Methods: Semi‐structured interviews were conducted with four surgeons, two anaesthesiologists, ten nurses and four physiotherapists in a single joint replacement centre during autumn 2018. The data were analysed using an inductive content analysis method. NVivo qualitative data analysis software was used. The COREQ checklist for qualitative studies was followed. Results: Our research addressed the gap in evidence by focusing on the four main parts of the patient journey in the selected context. Analysis of the data revealed nine main categories for the proposed eHealth needs: eligibility criteria, referrals, meeting the Health Care Guarantee, patient flow, postdischarge care, patient counselling, communication, transparency of the journey and receiving feedback. In addition, the requirements and further development needs for eHealth solutions were generally identified. Conclusions: From the point of view of healthcare professionals, eHealth solutions have huge potential in supporting the elective primary fast‐track hip and knee arthroplasty journey. However, it is important to acknowledge that these needs may be very different depending on the technological and organisational environment in question. Relevance to clinical practice: More effective use of information and communication technologies is needed for organisational optimisation resulting in a streamlined pathway, better access to healthcare services, improved outcomes and an improved patient experience. These results can be used in the development of new eHealth solutions to support surgical care journeys and patient education.